Long-Term Outcome After Out-of-Hospital Cardiac Arrest: An Utstein-Based Analysis - Baldi, Enrico; Compagnoni, Sara; Buratti, Stefano; Primi, Roberto; Bendotti, Sara; Currao, Alessia; Gentile, Francesca Romana; Sechi, Giuseppe Maria; Mare, Claudio; Bertona, Roberta; Raimondi Cominesi, Irene; Taravelli, Erika; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: No data are available regarding long-term survival of out-of-hospital cardiac arrest (OHCA) patients based on different Utstein subgroups, which are expected to significantly differ in terms of survival. We aimed to provide the first long-term survival analysis of OHCA patients divided according to Utstein categories. Methods: We analyzed all the 4,924 OHCA cases prospectively enrolled in the Lombardia Cardiac Arrest Registry (Lombardia CARe) from 2015 to 2019. Pre-hospital data, survival, and cerebral performance category score (CPC) at 1, 6, and 12 months and then every year up to 5 years after the event were analyzed for each patient. Results: A decrease in survival was observed during the follow-up in all the Utstein categories. The risk of death of the “all-EMS treated” group exceeded the general population for all the years of follow-up with standardized mortality ratios (SMRs) of 23 (95%CI, 16.8–30.2), 6.8 (95%CI, 3.8–10.7), 3.8 (95%CI, 1.7–6.7), 4.05 (95%CI, 1.9–6.9), and 2.6 (95%CI, 1.03–4.8) from the first to the fifth year of follow-up. The risk of death was higher also for the Utstein categories “shockable bystander witnessed” and “shockable bystander CPR”: SMRs of 19.4 (95%CI, 11.3–29.8) and 19.4 (95%CI, 10.8–30.6) for the first year and of 6.8 (95%CI, 6.6–13) and 8.1 (95%CI, 3.1–15.3) for the second one, respectively. Similar results were observed considering the patients discharged with a CPC of 1–2. Conclusions: The mortality of OHCA patients discharged alive from the hospital is higher than the Italian standard population, also considering those with the most favorable OHCA characteristics and those discharged with good neurological outcome. Long-term follow-up should be included in the next Utstein-style revision.